A sensitive strategy for the fluorescence detection of DNA methyltransferase activity based on the graphene oxide platform and T7 exonuclease-assisted cyclic signal amplification1. Issue 12 (21st June 2015) - Ma, Yefei; Chen, Lini; Zhang, Liangliang; Liao, Suqi; Zhao, Jingjin
<x xml:space="preserve">Abstract</x> A sensitive fluorescence detection method for DNA methyltransferase is developed based on graphene oxide and T7 exonuclease-assisted signal amplification.